(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research entitled (The approach of Sheikh Muhammad Al-Balisani in dealing with incorrect hadiths through his interpretation (Hossn Al-Bayan) - a descriptive study) is taken from his doctoral thesis as part of its requiremens. This research deals with Al-Balisani’s approach to dealing with weak hadiths and the most important conditions and controls that Sheikh Al-Balisani must deal with weak hadiths.It is an important topic in the science of hadith. Muhammad Al-Balisani cited in his interpretation a group of weak hadiths.The research relates to how to deal with hadiths that do not It reaches the level of authenticity due to the weakness of its transmission chain or text. We divided the research into three sections and a conclusion. In the first section، we talked about the life، In the second section، we began by defining the weak hadith، which is the hadith in which the conditions for the authentic hadith were not met، and defining the authentic hadith and the conditions for the authentic hadith. In the third section، we talked about the position of Al-Balisani on the hadith. Weak، and we mentioned some examples of this. Most of the time Al-Balisani comes up with weak hadiths and does not talk about them or refer to them. In conclusion، we mentioned the main findings we obtained after writing the paper.